LOVE FAILURE IN HAMKA’S NOVEL TENGGELAMNYA KAPAL VAN DER WICJK - ADI SUCIPTO (LP2MTBM MAKARIOZ, 2018)
This research is concerned with love failure in the novel Tenggelamnya Kapal Van Der Wijck written by HAMKA. The analysis is concern with the causes and effect of love failure of the main character in the novel, Zainuddin and Hayati because of the local custom which prevails in Batipuh village, Zainuddin is not allowed to get married with Hayati. He becomes very sad and disappointed. The causes of love failure which are analyzed include local custom and the appearance of the third person, whereas the effect of love failure is a deep disappointment in the heart of Zainuddin. The method used in this study is a qualitative research method which is supported by the procedures of collecting data and the techniques of analyzing the data